2003
DOI: 10.1002/em.10126
|View full text |Cite
|
Sign up to set email alerts
|

Using CTLL‐2 and CTLL‐2 bcl2 cells to avoid interference by apoptosis in the in vitro micronucleus test

Abstract: In vitro assays for chromosome aberrations (i.e., in vitro micronucleus and in vitro metaphase analysis tests) frequently produce false-positive or exaggerated-positive results. Our previous work suggested that apoptosis interferes with these tests, producing misleading results. These previous studies were conducted by performing the in vitro micronucleus test in CTLL-2 cells and a CTLL-2 cell derivative stably transfected with the apoptosis inhibitor gene bcl2. In the present study, these previous observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Clearly the number and classes of compounds analyzed needs to be expanded. Even so, these results are very encouraging, as the non-genotoxic cytotoxicants DEX and STS tend to be extreme challenges to mammalian cell genotoxicity assays [16][17]. Furthermore, we chose 24 hrs of continuous treatment as a particularly challenging experimental design to study, as previous work by lab L4 had demonstrated that assay specificity is reduced in this case [23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Clearly the number and classes of compounds analyzed needs to be expanded. Even so, these results are very encouraging, as the non-genotoxic cytotoxicants DEX and STS tend to be extreme challenges to mammalian cell genotoxicity assays [16][17]. Furthermore, we chose 24 hrs of continuous treatment as a particularly challenging experimental design to study, as previous work by lab L4 had demonstrated that assay specificity is reduced in this case [23].…”
Section: Discussionmentioning
confidence: 98%
“…Reports by Mentieres et al [16][17] and others suggest that the apoptotic program, perhaps especially nuclear fragmentation, can lead to the presence of MN-like events that may enhance the rate of false positive results. STS data presented here may represent a case in point, as elevated MN frequencies were observed by microscopy (L3).…”
Section: Apoptosis As a Confoundermentioning
confidence: 99%
“…The micronuclei were identified according to the criteria of Countryman and Heddle [23]: the size of the micronucleus is less than one-third of that of the main nucleus, the micronucleus lies within the cytoplasm of the cells, is surrounded by a distinct nuclear membrane and shows no overlapping or linkage to the main nucleus. No evidence for apoptosis, which may interfere with the micronucleus assay [24], was observed during the testing.…”
Section: Methodsmentioning
confidence: 86%
“…One of the hallmarks of apoptosis is DNA fragmentation into 50-300 kpb leading to oligonucleosomal fragmentation that can interfere with the results of clastogenic assays, leading to possible 'false positive' results [16,40] which provides an explanation for the false-positive results observed for curcumin but not for the reference mutagen MMS.…”
Section: Rodent Versus Human Follow Up Micronucleus Experiments (In Tmentioning
confidence: 94%
“…Rat liver S-9 (aroclor 1253 induced) Treatment times (h) o-Anthranilic acid [14,15] 137.14 118-92-3 + 3 Curcumin [16] 368.38 458-37-7 − 3 2,4-Dichlorophenol [14,17,18] 163.00 120-83-2 + 3 Ethyl acrylate [14,19] 100.12 140-88-5 − 24 or 30 Eugenol [14,20,21] 164.20 97-53-0 + 3 p-Nitrophenol [17] 139.11 100-02-7 + 3 Phthalic anhydride [17,18] 148.12 85-44-9 − 3 Propyl gallate [17] 212.20 121-79-9 − 3 and 24 or 30 1,3-Dihydroxybenzene (resorcinol) [17] 110.11 108-46-3 − 3 genotoxic potential which is not verified). In a review [1] of a large database of over 700 chemicals, the cumulative incidence of ' [4,5]) would prohibit such in vivo follow-up.…”
Section: Chemicalmentioning
confidence: 99%